Which Health Cares Are Related to the Family Physician? A Critical Interpretive Synthesis of Literature - Shahram YAZDANI; Maryam AKBARILAKEH (Tehran University of Medical Sciences, 2017)
Background: This study provided the theoretical basis for program development through a new conceptualization of the concept of family physician related health care. Methods: Critical interpretive synthesis (CIS) was used to carry out qualitative analysis and synthesis of the literature from 2006 until 2015. At the beginning of CIS, the search strategy was designed to access electronic databases such as CINAHL, Medline, Cochrane library, PsycINFO, Embase, EBMreviews, and Thomson scientific web of science database. The main review question was the clarification of the health care related to family physician in health system, which produced over related 750 articles; 60 articles related to the research objective were studied by purposive sampling. After identifying the main categories and sub-categories, synthesis of the contradictory findings in different studies was conducted. New concepts and relationships between concepts were created using CIS of documentation related to the place of family physician in health system. Results: To define the original position of family physician in health system, clarify its related health care and determine its boundaries from other health care providers, and its use in the design and development of family physician's educational program, a frame of concepts related to the main concept and question was created. A more useful means of understanding family physician is offered by the synthetic constructs of this framework. Conclusion: The theoretical conceptualization of family physician position and duties in the health system can be an appropriate guide for educational program and curricula in our context.